Quite a straightforward piece of maths I can't seem to get my head around here:

The tangent to the parabola at the point $(4a, 4a)$ is given by what equation?

Bearing in mind the parabola is $y^2 = 4ax$ and the general point $(at^2, 2at)$ lies on the parabola.

  • $\begingroup$ Do you know about implicit differentiation? You need to find the derivative first $\endgroup$ – Sam Weatherhog Nov 4 '15 at 21:37
  • $\begingroup$ @SamWeatherhog forgive me but what do I differentiate? $\endgroup$ – Pontius Pilate VII Nov 4 '15 at 21:39
  • $\begingroup$ @PontiusPilateVII You differentiate both sides of $y^2=4ax$ with respect to $x$. The left-hand side is done via the chain rule to get $2yy'$. $\endgroup$ – Arthur Nov 4 '15 at 21:42

Do you know how to compute the tangents to $y=\frac{1}{4a}x^2$ by differentiation? If we take the point $(t,\frac{1}{4a}t^2)$, the tangent has equation $$ y-\frac{1}{4a}t^2=\frac{1}{2a}t(x-t) $$ because the derivative of $x\mapsto \frac{1}{4a}x^2$ is $x\mapsto \frac{1}{2a}x$. For $t=4a$, we get $$ y-\frac{1}{4a}16a^2=\frac{1}{2a}4a(x-4a) $$ that is $$ y-4a=2x-8a $$ or $$ y=2x-4a $$

Just swap $x$ with $y$ and the requested tangent will be $$ x=2y-4a $$

Note that swapping $x$ with $y$ is an isometry, so it preserves tangents.

Let's make another example. Suppose you want to compute the normal to the parabola at the point $(a,-2a)$. You can do it in a very similar way, by computing the normal to the parabola $y=\frac{1}{4a}x^2$ at the point $(-2a,a)$. The tangent will be $$ y-a=\frac{1}{2a}\cdot(-2a)(x+2a) $$ or $$ y-a=-x-2a $$ that is $$ y=-x-a $$ The normal is thus $$ y=x-a $$ so the required normal is $$ x=y-a $$ (by swapping back $x$ with $y$).

  • $\begingroup$ @PontiusPilateVII If you swap $x$ with $y$ in your given equation, you get $x^2=4ay$, that is, $y=\dfrac{1}{4a}x^2$. $\endgroup$ – egreg Nov 4 '15 at 21:54
  • $\begingroup$ @PontiusPilateVII Where's the difference? An isometry also preserves angles. Don't change the question so that it invalidates existing answers. $\endgroup$ – egreg Nov 4 '15 at 22:26
  • $\begingroup$ Compute the tangent in the “swapped system”; the normal is easy to write; swap back. $\endgroup$ – egreg Nov 4 '15 at 22:29
  • $\begingroup$ @PontiusPilateVII At the end, of course. $\endgroup$ – egreg Nov 4 '15 at 22:32
  • $\begingroup$ @PontiusPilateVII I added the computation. $\endgroup$ – egreg Nov 4 '15 at 22:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.